Research and application of fiber-reinforced EPS particle lightweight soil in highway engineering in cold regions - Hechao Dou; Bo Xu; Fuxing Li; Yanan Li; Hongbo Liu; Fajin Zu (Scientific Reports)
Abstract In this study, the improvement effect of fiber-reinforced EPS (expanded polystyrene) granular lightweight soil was systematically investigated to address roadbed issues caused by severe cold climatic conditions, specifically, extremely low temperature of -20 °C and an average freezing depth of 92 cm—in Chaoyang City. The test results demonstrate that the use of lime as a curing agent significantly enhances the material’s performance while reducing overall cost. Standard compaction tests revealed a negative correlation between the dry density of the lightweight soil and the EPS content, with values ranging from 1.53 to 1.90 g/cm³. Unconfined compressive strength tests showed a decrease in strength with increasing EPS content; however, the incorporation of polypropylene fibers effectively compensated for this strength loss, achieving a peak compressive strength of 1.93 MPa. Freeze-thaw cycle tests (-18℃ to 20℃) confirmed the material’s excellent frost resistance, with significantly reduced strength loss and stabilized mass loss after multiple cycles. SEM analysis revealed a three–phase synergistic reinforcement mechanism characterized by “particle dispersion - fiber homogeneity - cementation reinforcement”. In this mechanism, the closed pore structure formed by EPS particles, the fiber network, and lime cementation products collectively enhances the internal stability of the material. Based on these findings, optimizing the mix proportions achieves a synergistic balance of lightweight, high strength, and frost resistance, providing an effective solution for roadbed engineering in cold regions.